Healthy Smartphone Use and Physical Activity Education as an Effort to Promote Mental Health Among School Adolescents - Alfiandari, A Dhini; Utama, Wirya Dipo (CV. Global Health Publication, 2026)
Adolescents are vulnerable to psychosocial problems due to academic pressure, developmental changes, and intensive exposure to digital technology. Excessive smartphone use and low levels of physical activity may negatively affect sleep quality, concentration, stress, and psychological well-being. This community service activity was conducted to improve students’ understanding of healthy smartphone use and physical activity as part of school-based mental health promotion. The activity employed an educative-participatory approach through interactive educational sessions, discussion, and health promotion media involving high school students. Educational materials included healthy digital behavior, the impact of sedentary lifestyles, the importance of physical activity, sleep quality, and simple stress management strategies. Students actively participated in the sessions and were able to identify the potential effects of excessive smartphone use and sedentary behavior on mental health. Participants also demonstrated increased awareness regarding balanced technology use and the importance of physical activity in daily life. These findings indicate that school-based education on healthy smartphone use and physical activity may serve as a practical promotive-preventive strategy to support adolescent mental health and improve mental health literacy among students.